2014
DOI: 10.1037/a0032509
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure, posttraumatic stress disorder symptomatology, and aggression in male juvenile offenders.

Abstract: Juvenile offenders have a high prevalence of trauma exposure and posttraumatic stress disorder (PTSD) symptoms, as well as aggressive behavior. However, relationships between exposure to different specific types of traumatic events, PTSD symptoms, and aggression have not been systematically investigated. Subgroups of male juvenile offenders were identified based on their self-reported exposure to different types of traumatic events. Male juvenile offenders who endorsed multiple types of trauma exposure or trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 32 publications
7
59
0
6
Order By: Relevance
“…This participant described the experience of trauma symptoms identified as outcomes of victimisation (Stimmel et al, 2014;Walsh et al, 2012), as a barrier to engagement with Victim Support, consistent with previous research (Alvidrez et al, 2008;Posick, 2014).…”
Section: Suffer From Depression Anyway So That Made It a Lot Worse supporting
confidence: 64%
See 1 more Smart Citation
“…This participant described the experience of trauma symptoms identified as outcomes of victimisation (Stimmel et al, 2014;Walsh et al, 2012), as a barrier to engagement with Victim Support, consistent with previous research (Alvidrez et al, 2008;Posick, 2014).…”
Section: Suffer From Depression Anyway So That Made It a Lot Worse supporting
confidence: 64%
“…This is a timely change in focus given that the Crime Survey for England and Wales (CSEW) recorded 1.9 million violent incidents in 2012/13 (Office for National Statistics, 2014). These figures suggest that there are a significant number of victims of violent crime each year who, as a result of their experiences, are at risk of developing trauma symptoms (e.g., avoidance behaviours, negative moods) which can subsequently lead to substance use problems, poor emotional regulation, and increased risk of psychiatric disorders (Davidson, Devaney and Spratt, 2010;Stimmel, Cruise, Ford and Weiss, 2014; Walsh, Danielson, McCauley, Saunders, Kipatrick and Resnick, 2012). These victimisation impacts are not limited to the specific time at which the crime occurs, but can also have long term consequences for psychological and physical health (Halligan, Michael, Clark and Ehlers, 2003).…”
mentioning
confidence: 99%
“…TRT, for example, was seen as facilitating the reframing of behaviour for staff as driven by underlying trauma rather than young people being blamed and responsible for their behaviour. This reflects a core theme within the growing trauma literature in secure and residential child care (Stimmel et al, 2014;Barron & Mitchell, 2017a). The most frequent codes suggest managers see the benefits of TRT delivered by programme staff as: (i) managers being more trauma-informed and aware of embedding trauma into public health policy; (ii) the growth in programme staff knowledge, skills and confidence including discussion of trauma in transition placement meetings; (iii) knowledge and skill gains for adolescents; (iv) the utilisation of a variety of ways to communicate with stakeholders about trauma; (v) that TRT is posts with a focus on a trauma perspective.…”
Section: Insert Table 1 Discussionmentioning
confidence: 99%
“…An earlier large scale survey of children in England identified 8.8% of children in residential (rather than specifically secure accommodation) presented with PTSD, 22% presented with emotional difficulties and 56.2% were identified as having a conduct disorder (Meltzer, Gatward & Corbin, 2003). In contrast, the levels of PTSD in juvenile detention in the US are over 50% (Wood, Foy, Goguen, Pynoos, & James, 2008;Stimmel, Cruise, Ford, & Weiss, 2014) and suicide rates are higher than in the general population (Bhatta, Jefferis, Kavadas, Alemagno, & Shaffer-King, 2014 (Abram et al, 2015).…”
Section: The Consequences Of Cumulative Traumamentioning
confidence: 99%
“…Likewise those who are subject to more than one type of trauma or incidents perpetrated by different people are also likely to fair less well (Follette, et al, 1996;Cabrera, Hoge, Bliese, Castro & Messer, 2007). This may be particularly the case when first traumatic exposure occurred in childhood (Finkelhor et al, 2011;Perkins & Graham-Bermann, 2012;Stimmel, Cruise, Ford & Weiss, 2014) where difficulties across attachment and relationships, emotional responses, dissociation, externalising or internalising behaviour, cognitions, selfconcept and sense of purpose (The National Child Traumatic Stress Network, 2015). This is also supported by research on revictimisation that has found that adult victims of violence have risk factors preceding the first police recorded violent victimisation (Faergemann, Lauritsen, Brink & Mortensen, 2010).…”
mentioning
confidence: 99%